La crítica hegeliana a la dimensión moral de la ironía en la Filosofía del derecho - Marchena, Julio (2021)
The notion of irony appears in Hegel’s Philosophy of Right as a figure of “moral evil” at the end of the second part referred to morality, with other notions such as hypocrisy, bad conscience, relativism, etc. While it is true, the Hegelian critics to the irony has a direct relationship with his critics to Schlegel’s romanticism in Hegel’s Lectures on Aesthetics and with the figure of spirit named “beauty soul” in the Phenomenology of Spirit, in the Philosophy of Right Hegel explores the moral dimension of this radical expression of subjectivity which will be required to be sublated from the standpoint of the ethical life.